Victimas en Medellín. Jornada de atención a víctimas del conflicto Medellín 2009 (2010)
In this paper, a characterization from the specific case of the file applied by the Forging Futures Foundation and the Assembly of Cooperation for Peace in Spain, Social Action, the prosecutor and the Ombudsman, Saint Bonaventure University, People's Training Institute is made, within the framework of the 9 district days to the attention to the victims of the armed conflict in the city of Medellin and the Metropolitan Area since May 2009